Legal History and the Development of Rights of Inhabitants of the West Bank since 1948 pursuant to International Law - Tomáš Mach (Journal on European History of Law, 2024)
The piece discusses the legal nature of the West Bank since 1948. It summarizes the history of the Territory since the British conquest from the Ottoman Empire in 1917 up till the 1994 Israel-Jordan peace treaty. Furthermore, it discusses the nature and development of the right to selfdetermination, ultimately arguing that the West Bank is currently terra nullius under Israeli occupation and that (leaving aside wishful thinking of different streams in international relations) under pure principles of customary international law there is no such think as Palestine, at least not in the territory of the West Bank.